Optimization of Workforce Placement in Box HEPA Production Using Workload Analysis Method to Fulfill Production Demand - Muhammad Nico Adriya; Handy Febri Satoto (Telkom University, 2026)
CV. XYZ experienced production inefficiencies due to workload imbalance among production departments, particularly in the Welding Division, resulting in bottlenecks, overtime, and the inability to consistently meet production demand. This study aims to determine the standard production time, evaluate worker workload, identify the optimal workforce allocation, and compare workforce planning alternatives to improve production efficiency. A quantitative approach was employed using direct observation, interviews, and stopwatch time studies involving 20 observations for each work element. Data were validated through uniformity and adequacy tests before calculating cycle time, normal time, standard time, and workload using the Workload Analysis (WLA) method. The findings indicate that the total standard production time for one Box HEPA unit is 217 minutes. Based on WLA, the production process requires six workers distributed across four production departments. Furthermore, capacity and cost planning identified an alternative workforce configuration consisting of four workers supported by planned overtime, reducing monthly labor costs from Rp 21,658,000 to Rp 15,379,030, resulting in a cost saving of Rp 6,278,970 (approximately 29%) while maintaining the required production capacity. The proposed approach enables a more balanced workload distribution, reduces labor inefficiencies, and supports better workforce planning in a make-to- order manufacturing environment. This study contributes by integrating time study, workload analysis, and capacity-cost planning into a practical decision-support framework that can assist small and medium-sized manufacturing enterprises in optimizing workforce allocation and improving operational performance.